Analisis Gaya Kepemimpinan Pada Kantor Camat Padang Utara - Rahmah Lila; Reni Marsalinda; Rifadhea Kurnia; Seselia Anjelini; Ririn Arianti; Wulandari Wulandari; Sri Rayahu Putri Gusva; Syamsir Syamsir (Departement of Mathematics Education, 2024)
The North Padang Subdistrict Office, as a government service agency, is in the public spotlight because of the various problems it faces. One of the main problems is the inadequate capacity of the apparatus in administering government. Apparatus who are less skilled and do not have adequate knowledge often become obstacles in carrying out their duties, so that efficiency and effectiveness in public services are hampered. Apart from that, the lack of sub-district apparatus resources to support the optimization of the implementation of activities is also a significant problem. In this research, the approach chosen is a qualitative research method with a descriptive approach. The population used in this research were all employees at the North Padang District Head Office, consisting of approximately 83 people. This population includes 75 civil servants, 6 contract workers, and 1 volunteer. The research results show that a leadership style that is oriented towards collaboration, empowerment and active participation from various parties has a very important role in overcoming public service problems at the North Padang District Head Office. In addition, the participatory leadership implemented by the North Padang Subdistrict Head has strengthened the relationship between the government and the community, as well as increasing the level of public trust and satisfaction with the public services provided.